“Murder in mykonos”: potentials and limitations of crime fiction literary tourism in Greece - Solakis, Konstantinos; Bellos, Konstantinos (My University, 2023)
Crime fiction literature is enjoyed worldwide for its intriguing mysteries and cultural references depending on the author's nationality or where the narrative takes place. The rising marketing trend of crime fiction literature significantly impacts literary tourism. Famous writers and their works are exploited by destination management organizations and used as a marketing tool; however, this is not happening in Greece. This research explores the sub-niche market of crime fiction literary tourism in Greece and focuses on its potential and limitations. To the best of our knowledge, this research is the first to explore the perspectives of crime fiction authors, publishers, and agents on the subject of crime fiction literary tourism, conducting qualitative research. The results indicate the lack of a national policy in the general market of literary tourism and the lack of understanding concerning the dynamics of crime fiction novels constituting tourism in Greece.
Keywords: Crime fiction; Destination marketing organizations; Greek tourism; Literary tourism; Tourism policy